Statements on chaos control designs, including a fractional order dynamical system, applied to a MEMS comb-drive actuator - Tusset, A. M.; Balthazar, José Manoel [UNESP]; Bassinello, D. G. [UNESP]; Pontes, B. R.; Palacios Felix, Jorge Luis (Springer, 2012)
In this work, we deal with a micro electromechanical system (MEMS), represented by a micro-accelerometer. Through numerical simulations, it was found that for certain parameters, the system has a chaotic behavior. The chaotic behaviors in a fractional order are also studied numerically, by historical time and phase portraits, and the results are validated by the existence of positive maximal Lyapunov exponent. Three control strategies are used for controlling the trajectory of the system: State Dependent Riccati Equation (SDRE) Control, Optimal Linear Feedback Control, and Fuzzy Sliding Mode Control. The controls proved effective in controlling the trajectory of the system studied and robust in the presence of parametric errors.
Keywords: Optimal control; SDRE control; Fuzzy sliding mode control; Chaos; MEMS; Fractional order